Improved reliable multilevel inverter for renewable energy systems - Sujatha M; A.K. Parvathy (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
New improved multilevel inverter (MLI) topology for Renewable energy systems is proposed in this paper. Cascaded multilevel inverters (CMLI) produce an output voltage level depending on the number of individual sources connected. The main drawback of CMLI is, as the output voltage level increases in number, the switches used in the device also increases and hence the complexity of the circuit increases. As the number of switches increases, the reliability of the circuit decreases. In this paper a novel MLI topology, which employs lesser number of switches, is proposed. A simulation model of CMLI and the proposed MLI has been built in MATLAB/SIMULINK. The reliability of the CMLI and the new topology MLI is analyzed by using MIL-HDBK-217.